Healthcare providers’ experiences and recommendations for antiretroviral therapy adherence in Ghana: A facility-based phenomenological study - Elvis Enowbeyang Tarkang; Emmanuel Manu; Fortres Yayra Aku; Joyce Komesuor; Veronica Charles-Unadike; Nelisiwe Khuzwayo; Judith Anaman-Torgbor (PLoS ONE, 2025)
Background In Ghana, poor treatment adherence among persons living with HIV (PLHIV) affects the effective treatment and management of HIV/AIDS. A key limitation in addressing the antiretroviral therapy (ART) adherence challenge is the skewed nature of the existing literature on the topic, as much of the research on ART adherence has focused on patient-reported experiences, failing to capture the perspectives of healthcare providers involved in ART delivery. Objective We ascertained healthcare providers’ perspectives on ART adherence among PLHIV and their proffered recommendations for improved ART retention in the Volta Region of Ghana. Methods A total of eighteen healthcare providers offering ART services to PLHIV in the Volta Region of Ghana were purposefully recruited from five HIV sentinel sites and interviewed. The data was thematically analyzed using ATLAS.ti. Results The health workers’ experiences were categorized under seven thematic areas. These included difficulties in accessing healthcare providers, improvements in adherence to treatment, people who have interrupted treatment often being new clients, general improvements in health outcomes, financial challenges, persistent stigmatization, and varied levels of family awareness about clients’ status. The reasons for treatment interruption were categorized into fifteen areas. These factors included appointment intervals, healthcare workers, medication shortages, long waiting times, clients’ distance from the facility, forgetfulness, drug characteristics, financial challenges, stigmatization, drug side effects, lack of donor support, alternative treatment choices, misconceptions about HIV cures, and the location of the ART clinic within the health facility. Participants recommended making health facilities/ART sites accessible to communities, increased advocacy on HIV by PLHIV, extended appointment intervals, continuous availability of antiretroviral drugs (ARVs), community support in the treatment of HIV, improved counseling, public education on HIV to reduce stigmatization, government support, home dispensing of ARVs, regulating the activities of traditional herbalists and faith-based healers, and the encouragement of religious bodies in ART adherence education for improved ART uptake. The ART-related challenges identified by the healthcare providers should be addressed by both the Ghana Health Service and the Ghana AIDS Commission to improve ART uptake and adherence in the Volta Region and across the country if Ghana is to end the HIV pandemic by 2030, as set by UNAIDS.